Implementation of digital modulation and demodulation algorithm using non-coherent FSK - Limaylla Chamorro, Kenny F. (2002)
This article develops a binary digital communication system that permit to send and receive audio files in wav format between two personal computers. Such a system employs coherent modulation FSK (Frequency Shift Keying) and Non Coherent FSK (because the phase of the carrier is unknown). Bevor the implementation, the modulation and demodulation algorithms were simulated usingMATLAB. The implementation, the exchange of data between two personal computers, has demonstarted good performance.